2021
DOI: 10.3390/insects12030207
|View full text |Cite
|
Sign up to set email alerts
|

Management of Onion Thrips (Thrips tabaci) in Organic Onion Production Using Multiple IPM Tactics

Abstract: Onion thrips (Thrips tabaci Lindeman) is a major pest in organic onion production and effective integrated pest management strategies are lacking. Our objective was to evaluate combinations of semi-glossy (“Rossa di Milano” and B5336AxB5351C) and waxy (“Bradley”) onion cultivars with reflective mulch, with or without biopesticides (spinosad + neem oil tank mix), to manage T. tabaci in organic onion production. Thrips densities were assessed weekly and bulbs graded and weighed at harvest. Onions sprayed with sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…Thrips infestation was significantly higher in unprotected plots than in protected plots. Onions sprayed with neem oil had fewer T. tabaci and produced higher yields than onions unsprayed, regardless of the onion cultivar (Iglesias et al, 2021). Botanicals possessed considerable differences in mortality rate and the efficacy of botanical showed that neem seed powder was significantly superior in efficacy (Tesfaye et al, 2021).…”
Section: Onion Thrips Infestation As Influenced By Interaction Of Var...mentioning
confidence: 98%
“…Thrips infestation was significantly higher in unprotected plots than in protected plots. Onions sprayed with neem oil had fewer T. tabaci and produced higher yields than onions unsprayed, regardless of the onion cultivar (Iglesias et al, 2021). Botanicals possessed considerable differences in mortality rate and the efficacy of botanical showed that neem seed powder was significantly superior in efficacy (Tesfaye et al, 2021).…”
Section: Onion Thrips Infestation As Influenced By Interaction Of Var...mentioning
confidence: 98%
“…Currently management of onion thrips is accomplished with the application of conventional insecticides. However, due to the unique characteristics of this pest, such as short generation time, cryptic behaviors and rapid reproduction, multiple applications of insecticides are required 8,9 . These repeated applications have various drawbacks, such as resistance development, residual and nontarget effects, cost, and hazards to human and livestock health 10 .…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the unique characteristics of this pest, such as short generation time, cryptic behaviors and rapid reproduction, multiple applications of insecticides are required. 8,9 These repeated applications have various drawbacks, such as resistance development, residual and nontarget effects, cost, and hazards to human and livestock health. 10 It is therefore essential to develop and use insecticides with novel modes of action that efficiently reduce the thrips populations while reducing hazardous effects on nontarget organisms and the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous strategies, including the application of fungicides and plant extracts have been tested against A.porri ( Jhala et al, 2017a;Yadav et al, 2017;Younas et al, 2021). Among all strategies, some are not economically applicable for the farmers because of their high cost whereas others have direct or indirect deteriorating and degrading effect on human beings and environment (Iglesias et al, 2021). Perfect method to overcome the maladies is the use of resistant onion genotypes.…”
Section: Introductionmentioning
confidence: 99%